Match-to-match variability of high-speed cctivities in Premier League soccer - Gregson, W.; Drust, B.; Atkinson, G.; Salvo, V. D. (International Journal of Sports Medicine, 2010)
The aim of the present investigation was to determine the between-match variability of high-speed running activities completed by a large sample of elite players over an extended period of time. A further aim of the study was to determine the influence of playing position on the magnitude of this variability. Observations on individual match performance measures were undertaken on 485 outfield players (median of 10 games per player; range=2-57) competing in the English Premier League from 2003/2004 to 2005/2006 using a computerised tracking system (Prozone®, Leeds, England). High-speed activities selected for analysis included total high-speed running distance (THSR), high-speed running (HSR), total sprint distance (TSD) and the total number of sprints undertaken. Total high-speed running distance in possession and without possession of the ball was also analysed. Match-to-match variability was generally high across all variables with a mean CV of 16.2±6.4% (95% CI=15.6-16.7%) and 30.8±11.2% (95% CI=29.9-31.7%) reported for HSR and TSD covered during a game. This variability was generally higher for central players (midfielders and defenders) and lower for wide midfielders and attackers. Greater variability was also noted when the team were in possession of the ball (~30%) than when they did not have possession (~23%). The findings of the present study indicate that match-to-match variability in performance characteristics of elite soccer players is high. This inherent variability means that research requires large sample sizes in order to detect real systematic changes in performance characteristics.